Plant community dynamics and carbon sequestration in Sphagnum‐dominated peatlands in the era of global change. Issue 10 (13th July 2020) - Oke, Tobi A.; Hager, Heather A.
Abstract: Aim: Hydroclimatic shifts and anthropogenic‐driven nitrogen deposition are major outcomes of global change that could compromise the functioning of many peatlands as a carbon sink. For Sphagnum ‐dominated peatlands, an emerging hypothesis is that the change could be triggered by shifts in competitive dominance among plant functional groups, specifically from the currently predominant decay‐resistant Sphagnum to the more decomposable vascular plants. However, the relationship between Sphagnum and vascular plant occurrence is notably complex and also includes facilitative interactions that are crucial to the productivity of Sphagnum, and therefore, carbon sequestration. Location: Global. Taxa: Northern peatlands— Sphagnum moss and vascular plants. Time period: Present day and the future. Methods: We use a conceptual review to examine underlying mechanisms for the competitive exclusion hypothesis and the nature of facilitative interactions between Sphagnum and vascular plants under potential global change conditions. We complement the review with an empirical study of peatlands with contrasting hydrology to provide some critical insights into the potential effects of change in plant communities on carbon sequestration. We also propose a conceptual model that presents probable combinations of global change factors and their implications for carbon sequestration. Results: Vegetation structure in Sphagnum ‐dominated peatland appears to be driven largely by hydrology, rather than competition among plant functional groups. The peat deposit also exerts some controls (e.g., nutrient immobilization) on biotic structure, thereby acting as resistance against an abrupt shift in plant communities. Main conclusions: Peatland controls that constrain vegetation shifts have developed over a millennial time‐scale in many peatlands, and the pace of climate change may not allow enough time for the establishment of those mechanisms in younger peatlands. Thus, the persistence of a given peatland as a carbon sink also likely depends on the successional stage of the peatland.